Degradation of Dual Image for Visual and near Infrared Spectrum at repeated CMYK/RGB Rendering - Agić, Darko; Stanimirović Žiljak, Ivana; Agić, Ana; Stanić Loknar, Nikolina (Journal of Graphic Engineering and Design, 2023)
A near infra red (NIR) designed image is a dedicated image containing additional information in a spectral domain between 700 and 1000 nm. Throughout management in visual spectrum z-parameter properties of selected separation or custom dyes are adjusted for NIR visualization. If such reproduced image is rescanned, Z-parameter properties of a CMYKIR designed image vanishes, or is seriously damaged.